The impact of institutions on the employment performance in European labour markets - Herbert S. Buscher; Christian Dreger; Raúl Ramos; Jordi Suri\~nach (Institute for the Study of Labor (IZA), 2005)
This paper investigates the role of institutions for labour market performance across European countries. As participation rates have been rather stable over the past, the unemployment problem is mainly caused by shortages in labour demand. Labour demand is expressed by its structural parameters, such as the elasticities of employment to output and factor prices. Institutional variables include employment protection legislation, the structure of wage bargaining, measures describing the tax and transfer system and active labour market policies. As cointegration between employment, output and factor prices is detected, labour demand equations are fitted in levels by efficient estimation techniques. To account for possible structural change, time varying parameter models and aysmmetries due to the business cycle situation are considered. Then, labour demand elasticities are explained by institutions using panel fixed effects regressions. The results suggest that higher flexibility and incentives of households to work appear to be appropriate strategies to improve the employment record. The employment response to economic conditions is stronger in a more deregulated environment, and the absorption of shocks can be relieved. However, the institutional database should be improved in order to arrive at more definite policy conclusions.
Keywords: E24; J23; J51; 330; EU employment; labour market institutions; Beschäftigung; Arbeitslosigkeit; Arbeitsmarktflexibilisierung; Arbeitsnachfrage; Elastizität; Schätzung; EU-Staaten